Analysis of transmission box vibration characteristics under random road torsional excitation. (October 2022) - Fu, Shengping; Luo, Shanming; Huang, Hanlin
Random road torsional excitation is a key excitation condition for transmission box vibration of tracked vehicles. In order to accurately analyze influences of random road torsional excitation on the vibration characteristics of the transmission box, a calculation method of this excitation for tracked vehicle is proposed based on the random expression of the roughness of standard road surface. Furthermore, random road torsional excitations under different road grades and vehicle speeds are simulated. With the finite element method and modal superposition method, the box body is discretized, and the elastic characteristics of the box body are characterized to explore the dynamics coupling mechanism of gear shafting and the box body. By considering bending-torsional coupling vibration of gear shafting under multi-source excitations, such as the fluctuated torque of engine and dynamic meshing stiffness of gears, dynamic coupling model of gear shafting and box body under random road torsional excitation is established. The dynamic response of the gearbox under random road torsion excitation is obtained by co-simulation with the variable step length Runge-Kutta method. Influences of different road grades, track preload and vehicle speeds on dynamic response characteristics of the gearbox are analyzed. Real vehicle road test scheme is designed to obtain surface acceleration response of the box body at different speeds on the cement road surface. Both test and simulation results are compared and analyzed to verify the accuracy of the simulation method, which provides a theoretical reference for dynamic optimization of the transmission box.